If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6 = 55 Reorder the terms: 6 + 6x = 55 Solving 6 + 6x = 55 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 55 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 55 + -6 6x = 55 + -6 Combine like terms: 55 + -6 = 49 6x = 49 Divide each side by '6'. x = 8.166666667 Simplifying x = 8.166666667
| 6x^2-2x-8= | | 0=21 | | X=7(r+3)(r-14) | | 4x^3-20x^2+16x= | | (B^3-4b^2)+(-4bI+16)= | | 5(m+1)=3(2m-2) | | rc+rx+bc+bx=0 | | 43+x=6+3x | | 20m^2+25m^3= | | 16+7x=-40 | | 20*20-90+40= | | 5x^2-39x+29=0 | | Z=8(x+h) | | 0.00000458=(x^2)/3.9 | | 4.58*10^-6=[2x]^2/[3.9-x] | | X^2+85x-13800=0 | | 75p^3+50p^2-12p-8=0 | | (w+2)(w^2-3w+4)= | | 4.58*10^-6=(2x)^2/(3.9-x) | | 0.2x+0.3y=8 | | 3x+5x=1 | | 6X^2-10x-44x=0 | | 7/12•1/4=5 | | 9.40=x/(1.78-x) | | 100-0.24= | | 2x-18+x=15 | | 3x-50+8x=1300 | | 7890^1/6 | | B^3-4b^2-4b+16= | | 6x+11-29=732 | | 2/9=t/6 | | 18+5n-9=2n+3 |